SIMULTANEOUS PRECIPITATION KINETICS OF KAOLINITE AND GIBBSITE AT 80°C AND PH 3 - Nagy K.L.; Lasaga A.C. (My University, 1993)
Precipitation rates of kaolinite and gibbsite were measured in stirred-flow reactors with a mixed seed substrate of kaolinite plus gibbsite at 80°C and pH 3. Input solutions were supersaturated simultaneously to different degrees with respect to both kaolinite and gibbsite. Rates were determined by assuming that each mineral precipitated only on its own seed. The calculated precipitation rates for each mineral are in good agreement with published data on the saturation state dependence of precipitation rates for each mineral alone (Nagy et al., 1991; Nagy and Lasaga, 1992). One rate for kaolinite was determined at a saturation state given by ΔGr = +1.11 kcal mol−1. This value doubles the range of saturation states at which kaolinite precipitation rates had been measured in the single-phase experiments. The new precipitation rates (mol m−2 s−1) for kaolinite support either a linear dependence of precipitation rate on solution saturation state for 0 ⩽ ΔGr ⩽ 1.11 kcal mol−1 given by , or a dependence derived from Transition State Theory given by Rateppt = (3.4 ± 0.91) × 10−13[1−exp{(−1.9 ± 1.4).The experimental technique shows promise for measuring precipitation rates of minerals in solutions supersaturated with respect to more than one phase. The results also indicate that a mineral preferentially will grow on itself. The gibbsite-like surface of kaolinite does not appear to serve as a nucleation site for gibbsite when gibbsite is also available for growth in solutions near equilibrium with respect to both minerals.